Self-esteem, emotional distress and sexual behavior among adolescent females: inter-relationships and temporal effects. - Ethier, Kathleen A; Kershaw, Trace S; Lewis, Jessica B; Milan, Stephanie; Niccolai, Linda M; Ickovics, Jeannette R (The Journal of adolescent health : official publication of the Society for Adolescent Medicine, 2006)
The current analyses attempt to clarify the relationship between psychological factors and sexual behavior. We test a model examining relationships between sexual history (e.g., age at initiation, partner history) and self-esteem and emotional distress (e.g., depression, anxiety, stress, hostility) and their impact on future sexual risk behavior (e.g., unprotected sex, multiple sexual partners).
Keywords: Adolescent; Adolescent Behavior; Emotions; Female; Humans; Interpersonal Relations; Risk-Taking; Self Concept; Sexual Behavior; Stress, Psychological; Time Factors